Thermal dimensioning of manufacturing moulds with multiple resistively heated zones for composite processing. (December 2017) - Weiland, JS; Hubert, P; Hinterhölzl, RM
Multi-zonal, electrically heated moulds for composite processing offer the potential of a direct heat introduction with low thermal lag and high energy efficiency. However, appropriate thermal dimensioning of these tools requires the consideration of the thermal response of the tool itself as well as the thermal and cure behaviour of the part, which is to date mostly estimated based on experience. To realize the full potential of this tool class, a numerical method is presented to determine a sound partitioning of the designated heating area utilizing 3D finite element cure simulation. Further, a cure simulation model of an application case is set up and validated. The capability of the numerical method to significantly increase the temperature accuracy and the degree of cure homogeneity are demonstrated in an evaluation of the numerically improved application case. Finally, the effect of the tool material on the zone allocations and temperature accuracy is studied.